1967
DOI: 10.1515/bchm2.1967.348.1.979
|View full text |Cite
|
Sign up to set email alerts
|

Der Gehalt an Tryptophan, Kynurenin, 3-Hydroxy-kynurenin und Ommochromen bei den überwinternden Eiern des SeidenspinnersBombyx moriwährend der Entwicklung

Abstract: Zusammenfassung: Die überwinternden Eier des Seidenspinners färben sich in den ersten Tagen purpurschwarz. Die Bildung der dafür verantwortlichen Ommochrome und die Konzentrationen der als Vorstufen für ihre Synthese geltenden Substanzen (Tryptophan, Kynurenin und 3-Hydroxy-kynurenin) wurden in Abhängigkeit von der Zeit ge-Summary: The hibernating eggs of the silkworm turn purple-black by the production of ornmochromes within the first four days after the egglaying. The concentrations of xanthommatine and ommi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Yolk cells and yolk granules change shape and their physical properties as part of the diapause process (Miya et aI., 1972). The most striking feature of the diapausing eggs is the dark coloration of the serosal cells due to the fonnation of ommochrome pigment (Koga and Osanai, 1967;Fig. 18.2).…”
Section: Embryogenesis Of Silkwormsmentioning
confidence: 99%
“…Yolk cells and yolk granules change shape and their physical properties as part of the diapause process (Miya et aI., 1972). The most striking feature of the diapausing eggs is the dark coloration of the serosal cells due to the fonnation of ommochrome pigment (Koga and Osanai, 1967;Fig. 18.2).…”
Section: Embryogenesis Of Silkwormsmentioning
confidence: 99%
“…It has been reported that the eggs and adult compound eyes of the silkworm Bombyx mori contain a combination of the ommochrome pigments, ommin and xanthommatin (Kawase and Aruga, 1954;Koga and Osanai, 1967;Linzen, 1974;Sawada et al, 2000). Many Bombyx egg and eye color mutants have been preserved and used to study insect genetics such as homologous recombination (Ariga and Murakami, 1975;Ariga and Murakami, 1976) and parthenogenetic induction (Hirokawa, 1993;Hirokawa, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, histidine is almost not metabolized during the pupal stage of Bombyx mori (Osanai and Kikuta, 1981). In contrast, phenylalanine, tyrosine and tryptophan could be metabolized and polymerized to various pigments (Koga and Osanai, 1967;Neehdam, 1978;Kayser, 1985;Umebachi, 2000). Pigments accumulated in the wing scales of butterflies, which are related to the excretion of nitrogenous substances, are regarded as storage excretory materials in "kidneys of accumulation" (Cochran, 1985).…”
Section: Discussionmentioning
confidence: 99%